Data Authentication for Web of Things (WoT) by Using Modified Secure Hash Algorithm-3 (SHA-3) and Salsa20 Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of the Web as a highly integrated user interface to real link things has brought many challenges and problems to study, which has led to a rapidly increasing area of research called the Web of things (WoT). Present Web of things (WoT) research is a trigger for the Internet of Things (IoT) growth, opening up opportunities to create ambient areas where people and things interact seamlessly via the Web. This proliferation created concerns among users about the increased usage of Web of Things (WoT) without ensuring that the data generated by its devices are maintained. Many ways to maintain authentication by using lightweight speed algorithms to encrypt and validate the relevant parameters. In the authentication of information, many algorithms have been developed to ensure that the data generated from a physical sensor to the user environment is authentic. These include SHA-1, SHA-2, SHA-3, etc. In Web of Things (WoT), it must be essential to ensure data validity and the continuation of data monitoring to ensure encryption and authentication speed. Therefore, the provision of fast algorithms is an essential requirement for the Web of Things (WoT). This paper includes a modification of the Secure Hash Algorithm 3 (SHA-3) with another high-speed algorithm (Salsa20), which creates a high-speed and secure algorithm in the sensor data validation process. The expanded logistic method would also produce the Secure Hash Algorithm 3 (SHA-3) algorithm's initial values unknown and not identifiable by the intruder. Correspondingly, the National Institute of Standards and Technology (NIST) fifteen statistical tests successfully surpassed the randomness of a proposed method